2014
DOI: 10.1038/ncomms6737
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast cooling reveals microsecond-scale biomolecular dynamics

Abstract: The temperature-jump technique, in which the sample is rapidly heated by a powerful laser pulse, has been widely used to probe the fast dynamics of folding of proteins and nucleic acids. However, the existing temperature-jump setups tend to involve sophisticated and expensive instrumentation, while providing only modest temperature changes of B10-15°C, and the temperature changes are only rapid for heating, but not cooling. Here we present a setup comprising a thermally conductive sapphire substrate with light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Preliminary work has focused on the impact of sequence-specific contributions to internal friction [20,8184]. Advances in nuclear magnetic resonance [8589] and single molecule spectroscopies [9092] combined with novel computational and theoretical methodologies [9395] should pave the way for comprehensive characterization of IDP dynamics and assessing their impact on the dynamical regulation of cellular phenotypes [96,97]. Overall, it is clear that continued synergistic investigations must be brought to bear in order to build on the insights that have been forthcoming with regard to connecting information encoded in IDP sequences to their form and function.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary work has focused on the impact of sequence-specific contributions to internal friction [20,8184]. Advances in nuclear magnetic resonance [8589] and single molecule spectroscopies [9092] combined with novel computational and theoretical methodologies [9395] should pave the way for comprehensive characterization of IDP dynamics and assessing their impact on the dynamical regulation of cellular phenotypes [96,97]. Overall, it is clear that continued synergistic investigations must be brought to bear in order to build on the insights that have been forthcoming with regard to connecting information encoded in IDP sequences to their form and function.…”
Section: Discussionmentioning
confidence: 99%
“…The hairpin loop is a secondary structural motif frequently observed in DNAs and RNAs that is involved in gene expression and regulation . A two‐state mechanism of DNA hairpin formation, where the hairpin DNA transits between a folded base‐paired state and an unfolded random‐coil state with the relaxation time ranging from several microseconds to hundreds of microseconds, has been well studied as an important system of DNA hybridization using fluorescence correlation spectroscopy (FCS), single‐molecule fluorescence resonance energy transfer (smFRET), single‐molecule force spectroscopy, and laser temperature jumping . These studies also suggested a complicated, multistate model of fast hairpin folding, which requires experimental techniques capable of probing both long‐ and short‐lived reaction intermediates in a wide range of detection times.…”
Section: Figurementioning
confidence: 99%
“…However, the ability to study DNA behaviour as a function of salt would allow quantitative comparison with a greatly expanded set of experiments, and, in particular, if we wish to apply oxDNA to biological systems, we would like to work at physiological salt ([Na + ] ≈ 0.15M). At the same time, the wealth of experimental data for the thermodynamic and mechanical properties of DNA as a function of salt concentration [47][48][49][50] makes fitting the saltdependent properties of an extended model possible.…”
Section: Introductionmentioning
confidence: 99%